Africa, Asia, and the History of Philosophy : Racism in the Formation of the Philosophical Canon, 1780-1830 - Park, Peter K. J. (Book collections on Project MUSE., 2013)
A historical investigation of the exclusion of Africa and Asia from modern histories of philosophy.